2017
DOI: 10.1088/1361-665x/aa57c9
|View full text |Cite
|
Sign up to set email alerts
|

Damage evaluation of fiber reinforced plastic-confined circular concrete-filled steel tubular columns under cyclic loading using the acoustic emission technique

Abstract: Glass-fiber reinforced plastic (GFRP)-confined circular concrete-filled steel tubular (CCFT) columns comprise of concrete, steel, and GFRP and show complex failure mechanics under cyclic loading. This paper investigated the failure mechanism and damage evolution of GFRP–CCFT columns by performing uniaxial cyclic loading tests that were monitored using the acoustic emission (AE) technique. Characteristic AE parameters were obtained during the damage evolution of GFRP–CCFT columns. Based on the relationship betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Figure 7 shows the average frequency (AF)-RA(i.e., the ratio of rise time to peak amplitude) correlation distribution of the RPC with and without nanofillers, hence identifying the RPC failure mode [34,35]. The RPC failure mode, regardless of whether or not nanofillers are incorporated, is the synergistic effect of shear failure and tensile failure, but dominated by the tensile failure.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 7 shows the average frequency (AF)-RA(i.e., the ratio of rise time to peak amplitude) correlation distribution of the RPC with and without nanofillers, hence identifying the RPC failure mode [34,35]. The RPC failure mode, regardless of whether or not nanofillers are incorporated, is the synergistic effect of shear failure and tensile failure, but dominated by the tensile failure.…”
Section: Resultsmentioning
confidence: 99%
“…Characteristic signal features such as peak amplitude, absolute energy or signal strength, are extracted and analysed in the time domain in order to assess damage growth on the specimens. This is a common approach when individual signal processing is not viable (see, e.g., Behnia et al 2014;Li et al, 2017). From the acquired AE signals, those containing zero PAC energy were subsequently removed from the data sets.…”
Section: Damage Evolutionmentioning
confidence: 99%
“…Specifically, for structures where cement-based material is present, AE focuses on damage quantification, source localisation and identification. Examples of such research works can be found in the literature (see, e.g., Farhidzadeh et al, 2013;Sagar and Rao, 2014;Li et al, 2017;Shi et al, 2018). This paper presents the results of a laboratory-based experimental campaign on the feasibility of AE for damage detection and condition evaluation on GCs.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies indicate that the AE technique is an effective means of detecting such structures. 18,[26][27][28][29] Farhidzadeh et al 26 proposed a probabilistic-based unsupervised pattern recognition algorithm to assess the soundness of the filled concrete in steel-concrete composite shear walls based on AE monitoring. Li et al 27 confirmed that the AE technique can be used to detect sleeve grout compaction in fabricated shear wall.…”
Section: Introductionmentioning
confidence: 99%
“…The test results show that the AE technique is effective in assessing the damage state of STCRC columns, including identifying damage thresholds, revealing damage mechanisms, and classifying damage patterns. Li et al 29 divided the uniaxial cyclic loading process of the fiber-reinforced plastic-confined circular CFST columns into three stages based on the AE signal analysis and proposed a modified damage index for quantitative evaluation of the damage degree of the specimens. Li et al 18 studied the bond-slip properties of the CFST columns by AE technique.…”
Section: Introductionmentioning
confidence: 99%